2006
DOI: 10.1177/1045389x06056953
|View full text |Cite
|
Sign up to set email alerts
|

Bidisperse Magnetorheological Fluids using Fe Particles at Nanometer and Micron Scale

Abstract: Conventional magnetorheological (MR) fluids are suspensions of micron-sized particles in a hydraulic or silicone oil carrier fluid. Recently, research has been conducted on the advantages of using bidisperse fluids, which are mixtures of two different powder sizes in the MR suspension. The MR fluids investigated here use a mixture of conventional micron- sized particles and nanometer-sized particles. The settling rate of such bidisperse fluids using nanometer-sized particles is reduced because the nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
130
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(134 citation statements)
references
References 17 publications
3
130
1
Order By: Relevance
“…To overcome these problems, many researchers studied various methods. Representatively, the coating magnetic particles with polymer not only decreases the density of magnetic particles but also well matches with lubricant medium oil [17]. Moreover, the abrasion for surface of the CI particles could be reduced during the reversing forming clusters of magnetic particles.…”
mentioning
confidence: 93%
“…To overcome these problems, many researchers studied various methods. Representatively, the coating magnetic particles with polymer not only decreases the density of magnetic particles but also well matches with lubricant medium oil [17]. Moreover, the abrasion for surface of the CI particles could be reduced during the reversing forming clusters of magnetic particles.…”
mentioning
confidence: 93%
“…The interaction between the particles impedes to a certain level of the shear stress without breaking and simultaneously increases the viscosity of the fluids [32]. In many cases, the effect of MRF is described by Bingham Plastic model [33]. A modified or extended Bingham model, or a combination of Bingham model with other models such as viscous and coulomb friction have also been used to describe the behaviour of MRF [34].…”
Section: Rheology Of Mrfmentioning
confidence: 99%
“…On the contrary, ferrofluids, which are stable dispersions of magnetic nanoparticles, show almost negligible rheological changes because magnetic attraction is dominated by Brownian motion [2]. Some attempts of increasing the strength of magnetic forces between microparticles have been done by dispersing them in a ferrofluid, and several authors have actually demonstrated that the field-induced yield stress could be substantially increased in this way [3][4][5]. In addition, it has been shown that suspensions of ferromagnetic microparticles in ferrofluids also exhibit a better colloidal stability against irreversible aggregation and sedimentation [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%